Interplay between Fungal Infection and Bacterial Associates in the Wax Moth Galleria mellonella under Different Temperature Conditions - Kryukov, Vadim Yu (J Fungi (Basel), 2020)
Various insect bacterial associates are involved in pathogeneses caused by entomopathogenic fungi. The outcome of infection (fungal growth or decomposition) may depend on environmental factors such as temperature. The aim of this study was to analyze the bacterial communities and immune response of Galleria mellonella larvae injected with Cordyceps militaris and incubated at 15 °C and 25 °C. We examined changes in the bacterial CFUs, bacterial communities (Illumina MiSeq 16S rRNA gene sequencing) and expression of immune, apoptosis, ROS and stress-related genes (qPCR) in larval tissues in response to fungal infection at the mentioned temperatures. Increased survival of larvae after C. militaris injection was observed at 25 °C, although more frequent episodes of spontaneous bacteriosis were observed at this temperature compared to 15 °C. We revealed an increase in the abundance of enterococci and enterobacteria in the midgut and hemolymph in response to infection at 25 °C, which was not observed at 15 °C. Antifungal peptide genes showed the highest expression at 25 °C, while antibacterial peptides and inhibitor of apoptosis genes were strongly expressed at 15 °C. Cultivable bacteria significantly suppressed the growth of C. militaris. We suggest that fungi such as C. militaris may need low temperatures to avoid competition with host bacterial associates.